Geology and Age Constraints on the Origin of the Intrusion-Related, Sheeted Vein-Type Åkerberg Gold Deposit, Skellefte District, Sweden - Kjell Billström; Benny Mattson; Ulf Söderlund; Hans Årebäck; Curt Broman (Minerals, 2012)
The Early Proterozoic (~1.9 Ga) Skellefte mining district in northern Sweden hosts abundant base metal deposits, but there are also gold-only deposits. The Åkerberg gold ore is unusual given the noted lack of alteration, a scarcity of sulfides and gold associated with thin (mm-cm wide) parallel quartz veins hosted in a gabbro. The gold content is positively correlated with the density of quartz veins, but gold often occurs between veins and also in parts of the gabbro where there is no veining. The gabbro is intruded by a granodiorite and associated pegmatite bodies, and U-Pb dating of zircon and baddeleyite suggest that these lithologies developed close in time at around 1.88 Ga ago. There are no primary inclusions in quartz veins, but different types of secondary aqueous inclusions occur. The Åkerberg ore is interpreted as a sheeted vein complex, with veins constrained to tensional cracks induced when a granodioritic magma intruded the competent, sheet-like gabbro intrusion. It is suggested that unmixing of the felsic magma also produced pegmatite bodies and a gel-like melt which invaded fractures in the gabbro and deposited silica. In a comparison, the Åkerberg ore shares many characteristics with the intrusion-related style of gold mineralizations.